The regulation of apoptotic cell death - Amarante-Mendes G.P.; Green D.R. (Brazilian Journal of Medical and Biological Research, 1999)
Apoptosis is a fundamental biological phenomenon in which the death of a cell is genetically and biochemically regulated. Different molecules are involved in the regulation of the apoptotic process. Death receptors, coupled to distinct members of the caspases as well as other adapter molecules, are involved in the initiation of the stress signals (The Indictment). Members of the Bcl-2 family control at the mitochondrial level the decision between life and death (The Judgement). The effector caspases are responsible for all morphological and biochemical changes related to apoptosis including the "eat-me" signals perceived by phagocytes and neighboring cells (The Execution). Finally, apoptosis would have little biological significance without the recognition and removal of the dying cells (The Burial).